2012
DOI: 10.31901/24566322.2012/04.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Medical Teachers toward Present Day Medical Education

Abstract: The relationships between adjustment problems and self-efficacy were investigated in a sample of 80 gifted students who were studying in 7th-10th enrolled at Salt Pioneer Center, using the adjustment problems scale and self-efficacy scale. The results indicated that the gifted students showed mid levels of adjustment problems. In addition, results showed a significant correlation between total scores of adjustment problems and self-efficacy. It showed there are indicated that no differences between self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…However there are still some reservations about design, planning, implementation and time limitations of the integrated curriculum. Dashputra et al reported 92% awareness of integrated curriculum which is similar to our study 6 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However there are still some reservations about design, planning, implementation and time limitations of the integrated curriculum. Dashputra et al reported 92% awareness of integrated curriculum which is similar to our study 6 .…”
Section: Discussionsupporting
confidence: 91%
“…In regional countries such as India and Nepal, integrated curriculum is also followed. Studies of medical teachers' perceptions have concluded that teachers agree to implement these curriculum reforms 6 . Integrated modular curriculum is a relatively new concept that began as a pilot project in 2001 with the assistance of the WHO in four medical colleges in Pakistan 7 .…”
Section: Introductionmentioning
confidence: 99%